Informational Performance of Audit Reports Content: Case of French Companies Listed on the Stock Exchange during the Decade 2010-2020 (Global Journal of Management and Business Research, 2022)
Abstract not found
Keywords: statutory auditor; audit report; information content; date of event; reservations